(untitled) (Indonesian Health Justice Review, 2024)
Indonesia’s health insurance program, particularly under its Universal Health Coverage (UHC) framework, has been a critical step toward achieving healthcare access for all. However, its effectiveness in promoting social justice remains contested, as certain populations still face barriers to comprehensive care. This paper assesses the UHC model’s impact on reducing health inequities, focusing on the accessibility, affordability, and quality of healthcare services. By analyzing policy documents, surveying healthcare beneficiaries, and evaluating healthcare providers’ experiences, the study explores how UHC has performed in both urban and rural settings. Findings suggest that while UHC has expanded insurance coverage, issues such as long waiting times, inadequate healthcare resources, and coverage exclusions still disproportionately affect marginalized populations, including the poor and those in remote regions. The paper concludes with recommendations for enhancing the equity and efficiency of Indonesia’s UHC system, including policy adjustments to address financial barriers and ensure equal treatment across socio-economic groups.